1998
DOI: 10.1074/jbc.273.33.20795
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of Inositol Trisphosphate but Not Cyclic Nucleotides in Visual Transduction in HermissendaEye

Abstract: Although several second messengers are known to be involved in invertebrate photoresponses, the mechanism underlying invertebrate phototransduction remains unclear. In the present study, brief injection of inositol trisphosphate into Hermissenda photoreceptors induced a transient Na ؉ current followed by burst activity, which accurately reproduced the native photoresponse. Injection of Ca 2؉ did not induce a significant change in the membrane potential but potentiated the native photoresponse. Injection of a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Initial investigations of transduction in invertebrate photoreceptors indicated that these were likely to use different mechanisms and offered the hope of an equally useful model system for studying different, but equally ubiquitous, cell-signaling pathways~see review, Yarfitz & Hurley, 1994!. activity, the subsequent steps, culminating in the cell membrane conductance changes, are less well agreed and may even be quite varied in different species~Brown Fein et al, 1984;Payne et al, 1986;Johnson et al, 1986;Payne et al, 1988;Bloomquist et al, 1988;Payne, 1990;Feng et al, 1991;Bacigalupo et al,1991;Ranganathan et al, 1995;Gomez & Nasi, 1998;Sakakibara et al, 1998;Dabdoub & Payne, 1999;Ukhanov & Walz, 2001!. activity, the subsequent steps, culminating in the cell membrane conductance changes, are less well agreed and may even be quite varied in different species~Brown Fein et al, 1984;Payne et al, 1986;Johnson et al, 1986;Payne et al, 1988;Bloomquist et al, 1988;Payne, 1990;Feng et al, 1991;Bacigalupo et al,1991;Ranganathan et al, 1995;Gomez & Nasi, 1998;Sakakibara et al, 1998;Dabdoub & Payne, 1999;Ukhanov & Walz, 2001!.…”
Section: Introductionmentioning
confidence: 99%
“…Initial investigations of transduction in invertebrate photoreceptors indicated that these were likely to use different mechanisms and offered the hope of an equally useful model system for studying different, but equally ubiquitous, cell-signaling pathways~see review, Yarfitz & Hurley, 1994!. activity, the subsequent steps, culminating in the cell membrane conductance changes, are less well agreed and may even be quite varied in different species~Brown Fein et al, 1984;Payne et al, 1986;Johnson et al, 1986;Payne et al, 1988;Bloomquist et al, 1988;Payne, 1990;Feng et al, 1991;Bacigalupo et al,1991;Ranganathan et al, 1995;Gomez & Nasi, 1998;Sakakibara et al, 1998;Dabdoub & Payne, 1999;Ukhanov & Walz, 2001!. activity, the subsequent steps, culminating in the cell membrane conductance changes, are less well agreed and may even be quite varied in different species~Brown Fein et al, 1984;Payne et al, 1986;Johnson et al, 1986;Payne et al, 1988;Bloomquist et al, 1988;Payne, 1990;Feng et al, 1991;Bacigalupo et al,1991;Ranganathan et al, 1995;Gomez & Nasi, 1998;Sakakibara et al, 1998;Dabdoub & Payne, 1999;Ukhanov & Walz, 2001!.…”
Section: Introductionmentioning
confidence: 99%
“…While this may be true for the photoreceptors of Drosophila , which are capable of an electrical response within 6 ms of a light stimulus (Hardie 1995), it is clearly not true of Limulus ventral photoreceptors. Our findings might also be relevant for photoreceptors of other slow-moving species, such as the file clam (del Pilar Gomez and Nasi 1998) and the marine mollusk, Hermissenda (Sakakibara et al 1998), where intracellular injection of InsP 3 has been also shown to induce rapid bursts of inward current or depolarization. However, the price of the amplification inherent in the Ca 2+ release mechanism may be a longer, more variable, latent period of the response in Limulus photoreceptors.…”
Section: Discussionmentioning
confidence: 65%
“…Among these six steps described above, the fifth step may be reconsidered. If the second messenger is generated by the photo‐stimulation open transduction channel just like invertebrate eye, the proposed model could be possible [13]. In this case it must be named as positive messengers, whereas reduction in second messenger opens the channel.…”
Section: Converting the Optical Signal To An Electric Signaling In Thmentioning
confidence: 99%